The Role of CD4 and CD8 T Cells in Human Cutaneous Leishmaniasis - da Silva Santos, Claire; Brodskyn, Cláudia Ida (Frontiers in Public Health, 2014)
Leishmaniasis, caused by infection with parasites of the Leishmania genus, affects millions of individuals worldwide. This disease displays distinct clinical manifestations ranging from self-healing skin lesions to severe tissue damage. The control of Leishmania infection is dependent on cellular immune mechanisms, and evidence has shown that CD4 and CD8 T lymphocytes play different roles in the outcome of leishmaniasis. Although the presence of CD4 T cells is important for controlling parasite growth, the results in the literature suggest that the inflammatory response elicited by these cells could contribute to the pathogenesis of lesions. However, recent studies on CD8 T lymphocytes show that these cells are mainly involved in tissue damage through cytotoxic mechanisms. In this review, we focus on the recent advances in the study of the human adaptive immunological response in the pathogenesis of tegumentary leishmaniasis.